Fetal growth scans –should i?. (18th April 2012) - Oniya, O; Ledingham, M; Duncan, A
Abstract : Background: The Audit of antenatal ultrasound scans in England and Wales in 2007 concluded that largest contribution to workload with potential for rationalisation was from the scans perform ed after the anomaly scan. They accounted for 27% of all scans and 63% of non-routine scans Methodolgy: Retrospective Audit of Growth scans performed in a Teaching Hospital. May 2011 Objectives: To determine amount, indications and frequency and to formulate a guideline for referral Results: Total number of scan was 500 in 202 patients. Range 1 to 11 scan per patient. Most scans were performed by Sonographers. In 46.5% scan had been planned as part of antenatal care while in 53.5% scans were unplanned. Indication was maternal in 105 cases and fetal in 97 cases. Average frequency interval was 2-4 weeks. Maternal indications varied from Medical disorders, antepatum haemorraghe and BMI issues to anxiety, cervical suture and abdominal trauma. Fetal indications varied from suspected IUGR and fetal abnormality to previous macrosomia, suspected polyhydramnios and suspected oligohydramnios Scan did not influence antenatal care in 78.2% and did not affect timing or mode of delivery in 86% Conclusion: The decision to perform growth scans poses a dilemma when the indication does not fall into a well defined category. Many of the growth scans performed did not fall under accepted indications. Appropriate use with careful consideration about frequency helps in the management of high risk women but random indications contributes significantly to the burden in most units